Developments in the value-added efficiency of South African workers – an exploratory study - C. Morris (South African Journal of Business Management, 2015)
Human capital efficiency (HCE) refers to an employee's ability to create value-added for his employer. The purpose of this study is to investigate the movement in HCE of the workers of South African listed companies over time. The metric for HCE, value-added human capital (VAHU), is calculated as the value-added per Rand spent on employee costs. The median of the compound annual growth rate of VAHU was calculated for all JSE Main Board and ALT-X listed companies, per industry, over the financial years ended 31 December 2001 to 30 June 2011. This median growth was used to infer an improvement or deterioration in HCE. HCE was found to have declined in all South African industries, except Consumer Services, from 2001 to 2011. The overall decline is attributable to an over-emphasis on tangible physical resources; excessive compensation levels imposed by the `strike' culture in South Africa; poor education and, possibly, to the overall economic decline after the global financial crisis of 2007. The government's drive for quality education has not translated into improved HCE. Companies may be forced to shoulder the cost of additional education and training themselves to further develop the basic skills of their employees.
Keywords: 650